New fixed point results in b-rectangular metric spaces - Roshan, Jamal Rezaei Rezaei; Parvaneh, Vahid; Kadelburg, Zoran (Nonlinear Analysis: Modelling and Control, 2016)
In this work, the class of b-rectangular metric spaces is introduced, some fixed point results dealing with rational type contractions and almost generalized weakly contractive mappings are obtained. Certain examples are given to support the results.
Keywords: generalized metric space; rectangular space; b-metric space; Geraghty condition; altering distance function